Teachers, education, community and professional learning tasks: A texture for the construction of professional knowledge - Quadros, Vera Cristina de; Carreira, Susana (Seven Editora, 2024)
This paper presents part of a research on the professional knowledge learned by teachers to teach algebra in the early years of Brazilian Elementary School, in a community of practice (CoP) context, mediated by professional learning tasks. Continuing education took place from March to May 2021, with 21 pedagogical teachers, in teaching activity, belonging to the staff of public servants of a municipal education network, in the interior of the state of Mato Grosso, Brazil. In this excerpt, we intend to discuss to what extent the development of professional learning tasks collaborated for the construction of professional knowledge of teachers participating in a CoP on the teaching of algebra to children. To this end, in addition to the theoretical framework, we present the proposal of teacher training carried out and, in sequence, in a qualitative interpretative approach, in the light of the social theory of learning and the theoretical model of mathematical knowledge for teaching, we discuss how the tasks of professional learning collaborated to the construction of professional knowledge for the teaching of algebra of this group of teachers. It can be inferred from the analysis that, in the context of the community of practice, the tasks of professional learning, more than mediation instruments, were decisive to provide the construction of professional knowledge to teachers. We hope that the discussions and shared results can contribute to the international debate on powerful proposals for the continuing education of teachers. DOI:https://doi.org/10.56238/sevened2024.009-011